What is a Present? - Hewson, John (Papers from the Annual Meetings of the Atlantic Provinces Linguistic Association (PAMAPLA) / ACTES DES COLLOQUES ANNUELS DE L’ASSOCIATION DE LINGUISTIQUE DES PROVINCES ATLANTIQUES (ACAALPA)., 1990)
When one defines the present in concrete cognitive terms, it is possible to explain differential usage between two different cognitive tense systems, such as those of English and French. There are certain differences of usage that are absolutely consistent between the two languages, showing quite clearly that what is in question is a difference in the underlying system, in this case the different cognitive representation of the present. A survey of all the different usage shows quite clearly that it all can be explained as the result of a single fundamental systemic contrast.